ANALISIS DETERMINAN FOREIGN DIRECT INVESTMENT DI NEGARA EMERGING MARKET ASIA PERIODE 2011-2015 - Nizar Eko Fachrulloh; Mukhammad Kholid Mawardi (Jurnal Administrasi Bisnis, 2018)
This study aims to investigate the determinants of FDI in Asian emerging market period 2011-2015. The framework was formulated into three groups with seven independent variables, ie Economic Conditions (Market Size and Trade Opennes); Host Country Characteristics (Tax Rate, Interest Rate and Infrastructure) and MNE Strategies (Political Risk and Human Capital). The type of research used is quantitative explanatory research with panel data of nine Asian countries based on purposive sampling technique. The method of analysis used is panel data regression. The results showed that simultaneously, the framework of determinant FDI significantly influenced the inflow of FDI into Asian emerging markets with Fstat of 70,67 and R2 of 0.96. Partially, Market Size, Trade Openness and Infrastructure have a positive and significant influence on FDI. Tax Rate has a negative influence as a determinant factor inhibiting FDI inflows. While Interest Rate, Political Risk and Human Capital have no significant influence on FDI. Based on result could be inferenced that the framework of determinant FDI which has formulated be able to explain the inflow of FDI in Asian emerging markets. Of the three groups of determinants, MNE Strategies is the weakest model because the two variables have no significant influence on FDI. Keywords: Determinan FDI, Emerging Market, MNE Strategies ABSTRAK Penelitian ini berusaha menyelidiki determinan FDI di emerging market Asia periode 2011-2015. Model yang dirumuskan terbagi menjadi tiga kelompok dengan tujuh variabel independen yaitu Economic Conditions (Market Size dan Trade Opennes); Host Country Characteristics (Tax Rate, Interest Rate dan Infrastructure) dan MNE Strategies (Political Risk dan Human Capital). Jenis penelitian yang digunakan adalah explanatory research dengan pendekatan kuantitatif. Data panel yang digunakan adalah sembilan negara emerging market Asia berdasarkan teknik purposive sampling. Metode analisis yang digunakan adalah regresi data panel model fixed effect. Hasil penelitian menunjukkan bahwa secara simultan, model determinan FDI berpengaruh signifikan terhadap masuknya FDI ke emerging market Asia nilai F hitung > F tabel (70,67366 > 2,27) dan Adjusted R2 sebesar 0,96. Secara parsial, Market Size, Trade Openness dan Infrastructure berpengaruh positif dan signifikan terhadap FDI. Tax Rate berpengaruh negatif dan signifikan sebagai faktor penghambat arus masuk FDI. Sedangkan Interest Rate, Political Risk dan Human Capital tidak berpengaruh signifikan terhadap FDI. Berdasarkan hasil penelitian dapat disimpulkan bahwa model determinan FDI yang dirumuskan mampu menjelaskan arus masuk FDI ke emerging market Asia. Dari ketiga kelompok determinan FDI, MNE Strategies merupakan model yang paling lemah, karena kedua variabelnya tidak berpengaruh signifikan terhadap FDI. Kata kunci: Determinan FDI, Emerging Market, MNE Strategies